PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PERCOBAAN PEMERKOSAAN - Dr. Henny Saida Flora, SH. M.Hum.M.Kn; Berlian SH.,M.Hum (Universitas Quality, 2021)
Rape is one of the many violations of human rights that often occur so that there is no reason that can justify it if it is contrary to the applicable rules, both from an ethical and religious perspective as well as law. Especially from a legal perspective, considering that Indonesia is a country based on law. Rape is a deprivation of human rights or deprivation of rights, such as the right to virginity, the right to be free from suffering, the right to be free from fear and inhumane behavior and with rape the victim has felt the consequences of human rights abuse.